Search for dark matter produced in association with a dark higgs boson in the bb[bar] final state using pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Rassloff, Damir Fabrice; Sauer, Christof; Schöning, André; et al. (Physical review letters, 2025)
A search is performed for dark matter particles produced in association with a resonantly produced pair of b - quarks with 30 < mbb < 150 GeV using 140 fb-1 of proton-proton collisions at a center-of-mass energy of 13 TeV recorded by the ATLAS detector at the LHC. This signature is expected in extensions of the standard model predicting the production of dark matter particles, in particular those containing a dark Higgs boson s that decays into bb[bar]. The highly boosted s → bb[bar] topology is reconstructed using jet reclustering and a new identification algorithm. This search places stringent constraints across regions of the dark Higgs model parameter space that satisfy the observed relic density, excluding dark Higgs bosons with masses between 30 and 150 GeV in benchmark scenarios with Z′ mediator masses up to 4.8 TeV at 95% confidence level.